Targeting HIV-1 reservoirs in T cell subsets - Li, Min; Budai, Marietta M.; Chen, Min; Wang, Jin (Frontiers in Immunology, 2023)
The HIV-1 reservoirs harbor the latent proviruses that are integrated into the host genome. It is a challenging task to eradicate the proviruses in order to achieve an HIV cure. We have described a strategy for the clearance of HIV-1 infection through selective elimination of host cells harboring replication-competent HIV (SECH), by inhibition of autophagy and promotion of apoptosis during viral re-activation. HIV-1 can infect various CD4+ T cell subsets, but it is not known whether the SECH approach is equally effective in targeting HIV-1 reservoirs in these different subsets in vivo. In a humanized mouse model, we found that treatments of HIV-1 infection by suppressive antiretroviral therapy (ART) led to the establishment of latent HIV reservoirs in naïve, central memory and effector memory T cells. Moreover, SECH treatments could clear latent HIV-1 reservoirs in these different T cell subsets of humanized mice. Co-culture studies showed that T cell subsets latently infected by HIV-1, but not uninfected bystander cells, were susceptible to cell death induced by SECH treatments. Our study suggests that the SECH strategy is effective for specific targeting of latent HIV-1 reservoirs in different T cell subsets.